Persepsi pegawai pemerintah mengenai faktor-Faktor yang mempengaruhi fraud di sektor pemerintahan kabupaten sidoarjo - Ningrum, Granita Dwi Matdia Suci; Triani, Ni Nyoman Alit (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of Internal Control, Enforcement of Regulations, Compensation Suitability, Organizational Commitment, and Organizational Ethical Culture on Fraud in the government sector of Sidoarjo Regency empirically. This study used quantitative method. This study used primary data that obtained from the distribution of questionnaires. The technique that had taken in this study is the census sampling technique (saturated sampling), so the research sample obtained 161 respondents including government employees who work in finance and procurement of goods/services at the Sidoarjo Regency government agency office. Based on the tests that had been carried out, the results of the study showed that the variables of regulatory enforcement, compensation suitability, and organizational ethical culture have a positive effect on fraud, while the variables of internal control and organizational commitment do not affect fraud.